The Models of Third Generation: Controversies on the Profound Nature of the Asian Crisis - MOUSSA, Wided BEN (Asian Development Policy Review, 2015)
This paper is consecrated to the literature review of the theoretical and empirical literature devoted to the outbreak of the Asian crisis in July 1997 which takes birth in Thailand on 2 July. Addressing the limits of the models of first and second generation giving a key role to the macro-economic fundamental, the models of third generation come to give a redefinition of vulnerability factors to crises by focusing on the imperfection of the financial markets and the risks of international banking liquidity.